Resepsi Al-Qur'an dalam Konstruksi Ruang dan Waktu Sakral : Studi Etnografi Khataman Jumat Legi di Makam Desa Tobai Timur, Sampang - Moh. Alfarizi Putra (Jurnal Moderasi, 2026)
The tradition of completing the recitation of the Qur’an every Friday Legi at the cemetery in Tobai Timur Village, Sokobanah, Sampang, is a religious practice known as “Khataman Jumat Manisan.” It has developed organically without formal coordination, yet takes place simultaneously across hamlets. This phenomenon has not yet been studied in depth from the perspective of the Living Qur’an, particularly regarding its dimensions of reception, symbolism, and social function. This study aims to analyze the practice, symbolic meanings, and functions of this tradition for the lives of the local community. The method employed is ethnography from James Spradley’s perspective, utilizing participant observation, in-depth interviews, and documentation at the research site. The findings reveal that this tradition originated from the transmission and transformation of the khataman practice from domestic spaces to the cemetery area around 2015, spearheaded by local figures. Symbolically, time (Friday Legi as sayyidul jumat) and space (the grave as ḥablun mina al-qubūr) are interpreted as a single spiritual unity that strengthens the community’s transcendental orientation by seeking blessings, reinforcing social solidarity, and serving as a means of transmitting spiritual and moral values. This study contributes to expanding the study of the Living Qur'an by demonstrating that the reception of the Qur'an is not merely textual but is also manifested in the construction of space, time, and social solidarity. Tradisi khataman Al-Qur’an setiap Jumat Legi di makam Desa Tobai Timur, Sokobanah, Sampang, merupakan praktik keagamaan yang dikenal sebutan “Khataman Jumat Manisan” dan berkembang organik tanpa koordinasi formal, namun berlangsung serempak lintas dusun. Fenomena ini belum dikaji secara mendalam dari perspektif Living Qur'an, khususnya menyangkut dimensi resepsi, simbolisme, dan fungsi sosialnya. Penelitian ini bertujuan menganalisis praktik, pemaknaan simbolik, dan fungsi tradisi tersebut bagi kehidupan masyarakat setempat. Metode yang digunakan adalah etnografi perspektif James Spradley, melalui observasi partisipan, wawancara mendalam, dan dokumentasi di lokasi penelitian. Temuan penelitian menunjukkan bahwa tradisi ini bermula dari transmisi dan transformasi praktik khataman dari ruang domestik ke area pemakaman sekitar tahun 2015, yang dipelopori tokoh-tokoh lokal. Secara simbolik, waktu (Jumat Legi sebagai sayyidul jumat) dan ruang (makam sebagai ḥablun mina al-qubūr) dimaknai sebagai satu kesatuan spiritual yang memperkuat orientasi transendental komunitas dengan mengharap keberkahan, memperkuat solidaritas sosial, dan berperan sebagai sarana transmisi nilai spiritual dan moral. Penelitian ini berkontribusi dalam memperluas kajian Living Qur'an dengan menunjukkan bahwa resepsi Al-Qur'an tidak hanya bersifat tekstual, tetapi juga terwujud dalam konstruksi ruang, waktu, dan solidaritas sosial.